Do cancer risk and benefit-harm ratios influence women's consideration of risk-reducing mastectomy? A scenario-based experiment in five European countries - Rebitschek, Felix G; Pashayan, Nora; Widschwendter, Martin; Wegwarth, Odette (PLoS One, 2019)
BACKGROUND: Personal cancer risk assessments enable stratified care, for example, offering preventive surgical measures such as risk-reducing mastectomy (RRM) to women at high risk for breast cancer. In scenario-based experiments, we investigated whether different benefit-harm ratios of RRM influence women's consideration of this, whether this consideration is influenced by women's perception of and desire to know their personal cancer risk, or by their intention to take a novel cancer risk-predictive test, and whether consideration varies across different countries. METHOD: In January 2017, 1,675 women 40 to 75 years of age from five European countries-Czech Republic, Germany, UK, Italy, and Sweden-took part in an online scenario-based experiment. Six different scenarios of hypothetical benefit-harm ratios of RRM were presented in accessible fact box formats: Baseline risk/risk reduction pairings were 20/16, 20/4, 10/8, 10/2, 5/4, and 5/1 out of 1,000 women dying from breast cancer. RESULTS: Varying the baseline risk of dying from breast cancer and the extent of risk reduction influenced the decision to consider RRM for 23% of women. Decisions varied by country, risk perception, and the intention to take a cancer risk-predictive test. Women who expressed a stronger intention to take such a test were more likely to consider having RRM. The desire to know one's risk of developing any female cancer in general moderated women's decisions, whereas the specific desire to know the risk of breast cancer did not. CONCLUSIONS: In this hypothetical scenario-based study, only for a minority of women did the change in benefit-harm ratio inform their consideration of RRM. Because this consideration is influenced by risk perception and the intention to learn one's cancer risks via a cancer risk-predictive test, careful disclosure of different potential preventive measures and their benefit-harm ratios is necessary before testing for individual risk. Furthermore, information on risk testing should acknowledge country-specific sensitivities for benefit-harm ratios.
Keywords: dospělí; Švédsko; Intention; Mastectomy; Prognosis; nádory prsu; Humans; Genetic Predisposition to Disease; genetická predispozice k nemoci; lidé středního věku; rozhodování; Middle Aged; Risk; Itálie; Czech Republic; Německo; Breast Neoplasms; riziko; Italy; prognóza; Risk Reduction Behavior; Surveys and Questionnaires; Česká republika; United Kingdom; Adult; Germany; průzkumy a dotazníky; ženské pohlaví; Spojené království; mastektomie; Decision Making; lidé; úmysl; Aged; senioři; chování snižující riziko; Sweden; Female